ROBERTO SIMONSEN AND THE INFLUENCES ON THE DEVELOPMENT OF SPORT AT SESI (Fiep Bulletin - online, 2013)
The Social Service of the Industry was first established in 1946 and one of the people responsible for its creation is Robert Simonsen. Since then, the SESI had promoted, among other activities, Sport activities. By means of our analysis, we confirm that in the decade of 1950 such sport activities may have suffered the influences of Simonsen's thought.
Keywords: Sport; SESI; Roberto Simonsen